2021
DOI: 10.3390/coatings11121548
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a High Water Flux Conductive MWCNTs/PVC Composite Membrane with Effective Electrically Enhanced Antifouling Behavior

Abstract: Membrane fouling is a major issue that deteriorates the performance of membrane filtration systems. The electrically assisted membrane filtration process is proven to be effective for alleviating membrane fouling. In this study, we synthesized an electrically conductive membrane by incorporating multiwalled carbon nanotubes (MWCNTs) into polyvinyl chloride (PVC). The synthesized membranes have larger porosity than the PVC membrane (incorporating polyethylene glycol (PEG)), and thus possess much higher water fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Although biofouling is more complex because of cell reproduction, it was found that the flux decrease for an electroconductive membrane was only caused by the deposition of bacteria, rather than bacterial attachment. 45,272,273 In contrast, the membranes without potentials failed to achieve a good antifouling performance and their flux recovery after cross-flow rinse. To illustrate the antifouling mechanism under electrochemical assistance, Jiang et al systematically investigated the antifouling behavior in both capacitor mode and resistor mode.…”
Section: Electrochemical Fouling Mitigation Fouling Monitoring and Re...mentioning
confidence: 99%
“…Although biofouling is more complex because of cell reproduction, it was found that the flux decrease for an electroconductive membrane was only caused by the deposition of bacteria, rather than bacterial attachment. 45,272,273 In contrast, the membranes without potentials failed to achieve a good antifouling performance and their flux recovery after cross-flow rinse. To illustrate the antifouling mechanism under electrochemical assistance, Jiang et al systematically investigated the antifouling behavior in both capacitor mode and resistor mode.…”
Section: Electrochemical Fouling Mitigation Fouling Monitoring and Re...mentioning
confidence: 99%